2010
DOI: 10.3758/app.72.3.591
|View full text |Cite
|
Sign up to set email alerts
|

Holistic processing underlies gender judgments of faces

Abstract: In three experiments, we investigated whether holistic processing underlies gender judgments about faces. Chinese participants were asked to make gender judgments for inverted, scrambled, or composite faces. Results showed that judgments were dramatically impaired by these manipulations (as compared with performance for normal upright faces), demonstrating three hallmark effects of holistic face processing that have been observed in perception of face identity. Whether the test faces were Chinese or Caucasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…This result is in line with the idea that when the whole face is available, gender discrimination requires holistic processing (Brown & Perrett, 1993;Zhao & Hayward, 2010) which is most efficient around the face center of gravity situated close to the nose (e.g., Bindemann, Scheepers, & Burton, 2009;de Heering et al, 2008). Note that this does not undermine the idea that some face parts might convey face gender better than others when presented in isolation, as recently reported (Best, Minshew & Strauss, 2010).…”
Section: Fixation Location and Facial Emotion Influenced Gender Discrsupporting
confidence: 88%
“…This result is in line with the idea that when the whole face is available, gender discrimination requires holistic processing (Brown & Perrett, 1993;Zhao & Hayward, 2010) which is most efficient around the face center of gravity situated close to the nose (e.g., Bindemann, Scheepers, & Burton, 2009;de Heering et al, 2008). Note that this does not undermine the idea that some face parts might convey face gender better than others when presented in isolation, as recently reported (Best, Minshew & Strauss, 2010).…”
Section: Fixation Location and Facial Emotion Influenced Gender Discrsupporting
confidence: 88%
“…Moreover, it seems that by reducing the number of invariant face cues varied, sex of the face became more salientfurther indication that the various cues seem to interactively affect face recognition. Female participants were significantly better at recognizing female faces than male faces, suggesting that sex cues were processed in other-race faces, as well as own-race faces (see also Zhao & Hayward, 2010).…”
Section: Resultsmentioning
confidence: 88%
“…None of the studies demonstrated whether the gender judgement task employed involved holistic processing. This is especially important, given that facial gender recognition, like identity recognition, shows evidence of configural and holistic processing (Baudouin & Humphreys, 2006;Zhao & Hayward, 2010).…”
Section: Facial Gender Perception In Prosopagnosiamentioning
confidence: 98%